Fundamentals of creep in metals and alloys - Kassner, Michael Ernest (Elsevier, 2009)
Creep refers to the slow, permanent deformation of materials under external loads, or stresses. It explains the creep strength or resistance to this extension. This book is for experts in the field of strength of metals, alloys and ceramics. It explains creep behavior at the atomic or "dislocation defect" level. This book has many illustrations and many references. The figure formats are uniform and consistently labeled for increased readability. This book is the second edition that updates and improves the earlier edition. .Numerous line drawings with consistent format and units allow easy comparison of the behavior of a very wide range of materials. Transmission electron micrographs provide direct insight into the basic microstructure of metals deforming at high temperatures. Extensive literature review of about 1000 references provides an excellent overview of the field.